ChemInform Abstract: Preparation and Stability of a New Compound SrCe0.9Lu0.1O2.95. Issue 16 (April 2015) - Matskevich, N. I.; Wolf, Th.; Vyazovkin, I. V.; Adelmann, P.
Abstract SrCe0.9Lu0.1O2.95 is prepared by solid‐state reaction of ball milled powders of SrCO3, CeO2 and Lu2O3 (1100‐1800 °C).